The implementation of health coaching among people with mental disorders: A scoping review - Andriani Andriani; Ah Yusuf; Rizki Fitryasari; Irma Iryanidar; Kusrini S. Kadar (Journal of Public Health and Development, 2026)
People with mental disorders often face the complexity of both physical and mental health issues which can cause various negative impacts on patients and those around them. Therefore, appropriate strategies are needed to overcome these various impacts. Health Coaching is an appropriate strategy to address these issues. This scoping review aims to explore existing research about the implementation of health coaching for people with mental disorders (benefits and implementation methods). The search for articles was conducted across several databases, namely Scopus, Embase, PubMed, The Cumulative Index to Nursing and Allied Health Literature (CINAHL), and citation searching. We used review guidelines from The Joana Briggs Institute (JBI). We utilized the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Review (PRISMA-ScR) guidelines to ensure that this review is systematic, structured, transparent, and used ‘Convidence Support’ tools to organize and analyze the data. Searches turned up 708 studies. Twenty studies were found for data extraction and analysis after the full-text review process. Information was compiled and shown in 3 themes for benefits (reduced symptoms and improved mental health, improved physical activity and healthy, and effectiveness-economics benefits) and 2 for implementation methods (delivery modes and techniques). The analysis of 20 articles led to the conclusion that health coaching can be a tactical choice that improves the mental illness patients' physical and psychological circumstances. This is due to the various benefits of health coaching and its highly diverse methods of implementation, both in terms of delivery modes and techniques.